2004
DOI: 10.1007/s00464-003-9311-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and postoperative levels of interleukin-6 in patients with acute appendicitis: comparison between open and laparoscopic appendectomy

Abstract: The operative stress in open as compared with laparoscopic appendectomy is not reflected by circulating levels of IL-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…parameter (ratio) = parameter postsurgery /parameter presurgery similar to other studies. 19 Univariate correlation analysis was performed by Spearman's rank correlation method using these relative changes (ratios). Afterwards, multivariate linear regression analysis was performed as described previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…parameter (ratio) = parameter postsurgery /parameter presurgery similar to other studies. 19 Univariate correlation analysis was performed by Spearman's rank correlation method using these relative changes (ratios). Afterwards, multivariate linear regression analysis was performed as described previously.…”
Section: Discussionmentioning
confidence: 99%
“…In study population 2, differences in FGF‐21 serum concentrations and other laboratory parameters before and after renal surgery were assessed by Wilcoxon signed‐rank test for related samples. Furthermore, relative changes (postsurgical‐to‐presurgical ratios) were calculated for all laboratory parameters as follows: parameter (ratio) = parameter postsurgery /parameter presurgery similar to other studies . Univariate correlation analysis was performed by Spearman's rank correlation method using these relative changes (ratios).…”
Section: Methodsmentioning
confidence: 99%
“…Presumably, the concentration of IL-6 in blood increases after surgery in correlation with the degree of surgical stress; but in perforated appendicitis, this leads to an IL-6 expression rate more than 2.5-times that of the reference levels in 90% of such patients [11][12][13]. Despite the promising results of systematic reviews devoted to the use of IL-6 in AA diagnosis, the nature of the enzyme-linked immunosorbent (ELISA) method means that it will not be available in routine tests in admissions for some time.…”
Section: Introductionmentioning
confidence: 96%
“…IL-6 is a mediator of the inflammatory response and early marker of tissue damage. 2,30 Eriksson et al also reported a very high serum concentration of IL-6 in patients with complicated appendicitis. 26 Kharbanda et al believe that an understanding of the fluctuations in biomarker levels in relation to the duration of abdominal pain may be clinically useful.…”
Section: Discussionmentioning
confidence: 97%